Analisa Image Quality pada Variasi Nilai Sensitivity Encoding MRI Brain Sekuens T1 TSE Axial di instalasi Radiologi RSUP Prof. dr. I.G.N.G.Ngoerah Denpasar - Nelce Silvia Panggaliau; I Made Lana Prasetya; I Made Adhi Mahendrayana (STIKes Ibnu Sina Ajibarang, 2023)
Magnetic resonance imaging (MRI) is an advanced medical device in the medical field that combines computer technology, high magnetic fields (0.064-7.0 Tesla), and radio waves to create cross-sectional images of the human body. Magnetic resonance imaging (MRI) examination has advantages over other diagnostic methods, because it does not use ionizing radiation, is non-invasive, produces high resolution in soft tissues, and allows different slice marks in all planes (axial, sagittal, coronal, even oblique), so that the image results are more detailed and clear. Sensitivity Encoding is a parallel imaging technique that uses images generated from a phased array coil. SENSE reconstruction can speed up the filling of the K Space thereby reducing scan time. In MRI brain imaging, a clear contrast between organs and minimal noise is required, so a good CNR (Contrast to Noise) is needed. CNR is derived from SNR. CNR is the difference in value between two SNRs that are close to each other. The type used is quantitative research with an experimental approach. The samples of this study were 10 MRI brain patients who underwent examinations in June-July 2023 at the Radiology Installation of Prof. Dr. I. G. Ngoerah Denpasar Hospital. G. N. G. Ngoerah Denpasar The results of this study show a sig value of 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected. This means that there is a significant difference in Contrast to Noise Ratio (CNR) on MRI examination of Brain T1 TSE Axial sequences using variations in Sensitivity Encoding values. Sensitivity Encoding value 2 is able to produce a more optimal CNR compared to the Sensitivity Encoding value, seen from the meank rank value at Sensitivity Encoding value 2 which is 55.2325 while at Sensitivity Encoding 3 is 42.8033. There is a difference in Contrast to Noise Ratio (CNR) on MRI Brain examination of T1 TSE Axial sequences by using variations in Sensitivity Encoding values 2 and 3. The Sensitivity Encoding value that can provide the most optimal Contrast to Noise Ratio (CNR) on MRI Brain examination of T1 TSE Axial sequences is Sensitivity Encoding value 2.